Optical guiding-based cell focusing for Raman flow cell cytometer. Issue 11 (14th May 2018) - Verma, Ravi Shanker; Ahlawat, Sunita; Uppal, Abha
Abstract : We report the use of an optical guiding arrangement generated in a microfluidic channel to produce a stream of single cells in a line for single-cell Raman spectroscopic analysis. Abstract : We report the use of an optical guiding arrangement generated in a microfluidic channel to produce a stream of single cells in a line for single-cell Raman spectroscopic analysis. The optical guiding arrangement consisted of dual-line optical tweezers, generated using a 1064 nm laser, aligned in the shape of a ' ' symbol. By controlling the laser power in the tweezers and the flow rate in the microfluidic channel, a single line flow of cells could be produced in the tail of the guiding arrangement, where the 514.5 nm Raman excitation beam was also located. Furthermore, by resonantly exciting the Raman spectrum, a good-quality Raman spectrum could be recorded from the flowing single cells as they passed through the Raman excitation focal spot without the need to trap the cells. As a proof of concept, it was shown that red blood cells (RBCs) could be guided to the tail of the optical guide and the Raman spectra of the resonantly excited cells could be recorded in a continuous manner without trapping the cells at a cell flow rate of ∼500 cells per h. From the recorded spectra, we were able to distinguish between RBCs containing hemoglobin in the normal form (normal-RBCs) and the met form (met-RBCs) from a mixture of RBCs comprising met-RBCs and normal-RBCs in a ratio of 1 : 9.